The influence of Electronic Innovation on Performance Of Three To Five Star Hotels in Kenya. - Gioko, sylvia (Advances in Social Sciences Research Journal, 2021)
Electronic innovation influence on performance of three to five star hotels in Kenya Sylvia Mukenyi Gioko Department of Business Administration, Jomo Kenyatta University of Agriculture and Technology, Nairobi, Kenya Elegwa Mukulu College of Human Resource Development, Jomo Kenyatta University of Agriculture and Technology, Nairobi, Kenya Oloko Margarate Department of Business Administration, Jomo Kenyatta University of Agriculture and Technology, Nairobi, Kenya Abstract The hotel industry heavily depends on the development of information systems so as to adapt technology, which is the single greatest force driving change in the hospitality industry .The role of innovation in the contemporary hotel industry is significantly important in sustaining competitive advantage, innovation in the hotel industry enables hotels to adopt novel ideas, improve service processes, and enhance operational efficiency levels. It also helps the hotels in meeting the needs of their customers, earn sales and achieve profitability, engage in corporate social responsibility and maintain competitive advantages in rapidly-changing markets. The Kenya tourism sector experienced loss of revenue of 74 percent indirect international tourism receipts for 2020 translating to 37 billion shillings (336 million US dollars) loss against projected revenue of 1.34 billion dollars for the review period. In light of these, this study sought to establish the influence of e-innovation on performance of three to five star hotels in Kenya. The study adopted a descriptive form of research design. In addition, a qualitative research approach was utilized. The target population for the study was the one hundred and twelve three to five star hotels in Kenya. Multiple regression model was used to draw inference from the data collected. The Statistical Package for Social Science (SPSS) was utilized for statistical analysis. Findings reveal that e-innovation had an average of 3.7023 with a standard deviation of 0.41903. In addition, there was a significant R square value of 0.362 between e-innovation and performance of three to five star hotel. This suggests that 36.2% of variation in hotel performance is explained by e-innovation. The study recommend that greater focus on e-innovation in hotels could bring competitive advantage through increase of number of online purchases, raised customer satisfaction by time-saving. Key words: Electronic innovation, Electronic customer relationship management, Performance